Preparation of nobiletin in self-microemulsifying systems and its intestinal permeability in rats - Yao, Jing; Lu, Yun; Zhou, Jian Ping (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
ABSTRACT: PURPOSE. The objective of this study was to prepare nobiletin self-microemulsifying drug delivery systems (SMEDDS) and investigate its intestinal transport behavior using the single-pass intestinal perfusion (SPIP) method in rat. METHODS. The characterizations of nobiletin SMEDDS were investigated. SPIP was performed in each isolated region of the small intestine (i.e. duodenum, jejunum, ileum and colon) over three concentrations of nobiletin (15, 30 and 60 µg/ml) at a flow rate of 0.2 ml/min. The concentrations of the samples were determined by HPLC and the effective permeability coefficients (Peff) in rats were calculated. Considering the high correlation of rat Peff values with those of human, the human intestinal permeability was predicted using the Lawrence compartment absorption and transit model. The intestinal permeability of nobiletin in SMEDDS, sub-microemulsion and micelles was compared. RESULTS. The particle size and zeta potential of nobiletin SMEDDS were (28.6±0.3) nm and (–22.6±3.5) mV, respectively. The Peff in jejunum at 15 µg/ml was significantly higher than that at 60 µg/ml (p< 0.01). The Peff in colon was higher at the same concentration comparing to the other intestinal segments. Moreover, there was no statistical difference in Peff at each same concentration in jejunum, duodenum and ileum. The estimated human absorption of nobiletin for the SMEDDS dilutions was higher than that for sub-microemulsions (p<0.01) and similar to that of the micelles (p>0.05). CONCLUSIONS. Bases on the above results, the SMEDDS could enhance the intestinal permeability of the nobiletin, and may be presented as potential candidates for improving the oral absorption of the noblietin. KEYWORDS. Nobiletin; Single-pass intestinal perfusion; Self-microemulsifying; Intestinal permeability